Law, Justice and Democracy in a Liberal Order According to F. A. Hayek - Paz, Anderson (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
This paper aims to discuss the concept of law, justice and democracy in a liberal order for F. A. Hayek. Exploratory methodology is used through a bibliographic review that focuses mainly on the hayekian work Law, Legislation and Liberty. The notions of rules of just conduct, of discovering the laws and the role of the judge, non-social justice and demarquia as a return to the democratic ideal will be highlighted. The Hayeks’s aim was to prevent Western societies from entering the road to serfdom. However, the relationship between the law, democracy and justice in Hayek raises important questions and criticisms, namely, freedom and justice are conceived only in their negative sense, democracy is understood only in the formal and procedural sense, and the judge assumes the role of Hercules in the discovery of the most appropriate norm for specific cases.